(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The purpose of this study is to determine the level of mathematics anxiety in primary school teachers in Turkey and to investigate the influence of a number of variables over the anxiety level. 559 teachers were participated in the study. In this study, mathematics Anxiety Scale Intended for Teachers and Candidate Teachers (MKÖ-Ö) was used as the data collection tool. For data analysis, "t" test, analysis of variance (ANOVA), and Tukey test were applied. According to the research results, we have found that total anxiety scores for teachers were at the “I am anxious a little” level. Also, there was a significant difference between teachers’ anxiety level and gender variable, and female teachers’ anxiety levels were found to be higher than male teachers. Additionally, teachers’ anxiety levels decreased as their age and tenure increased. According to the variable of the program of study, the anxiety levels of teachers who graduated from primary school teaching program were lower than the graduated teachers from other programs. Moreover, it is found that the anxiety levels of mathematics teachers who like their job were lower than those who do not like their job.